IAMSAR manual International Aeronautical and Maritime Search and Rescue Manual (International Maritime Organization ; Montreal : International Civil Aviation Organization, 2019)
The Organization and Management volume discusses the global SAR system concept, establishment and improvement of national and regional SAR systems and cooperation with neighbouring States to provide effective and economical SAR services. The 2019 edition incorporates amendments adopted by ICAO and approved by the IMO Maritime Safety Committee. The 2018 amendments enter into force on 1 July 2019